Nutrition and Liver Disease - Pietro Vajro (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2018)
Malnutrition in people with liver disease is a challenging issue due to its multifactorial nature, which includes hypermetabolism, increased energy needs, malabsorption, and anorexia. Despite advances in both assessment and management, correct nutritional support is still an often-unanswered need in the care of these patients to avoid poor outcomes. One of the central issues remains how to improve muscolar mass of sarcopenic chronically malnourished individuals with end stage liver diseases and cirrhosis, as only a correct nutritional assessment and subsequent nutritional handling may enhance quality of life and disease outcome. Nutritional management is mandatory in certain inherited metabolic/genetic defects: in these patients specific dietary restrictions/supplementations represent a challenge to guarantee optimal growth and liver health. A nutraceutical approach dealing with hepatoprotective effects of specific nutrients, has been proposed for several chronic liver disease, mainly in obesity related liver disease and alcoholic liver disease. Finally, other challenges are represented by tailored nutritional intervention in improving gut-liver axis dysfunction also in parenteral nutrition/intestinal failure associated liver disease, inflammatory bowel disease, and celiac disease. The purpose of this Special Issue, "Nutrition and Liver Disease", is to provide novel information and perspectives in the field of nutrition in liver disease and its management.